The effect of low- and moderate-intensity interval training on cognitive behaviors of male and female rats with VPA-induced autism - Sabet Nazanin; Abadi Banafshe; Moslemizadeh Amirhossein; Rajizadeh Mohammad Amin; Arabzadeh Fatemeh; Vakili Shahrbabaki Sajjad S.; Soltani Zahra; Rafie Forouzan; Bashiri Hamideh (Elsevier Ltd, 2025)
Introduction
This study was performed to evaluate the effects of low and moderate treadmill exercise for one month on social interaction, anxiety-like behaviors, and spatial learning and memory in male and female autistic rats.
Methods
Pregnant rats received valproic acid (VPA) (600 mg/kg/i.p) once on gestational day 12.5 to induce autism-like symptoms in the offspring. After delivery, the offspring were divided into six main groups, each with male and female subgroups: Control (CTL, prenatal normal saline), autism (prenatal VPA), low-intensity training (LIT,normal saline + low treadmill exercise), moderate -intensity training (MIT, normal saline + moderate treadmill exercise), VPA + LIT, and VPA + MIT. On the 60th day, the offspring were tested by the elevated plus maze (EPM), open field test (OFT), social interaction test (SIT), and Morris water maze (MWM).
Results
The results showed that both LIT and MIT could partly alleviate anxiety-like behaviors induced by prenatal VPA exposure in two sexes. Social impairment was observed in the autistic rats and was improved by LIT in both sexes and MIT in females. No significant change was seen in the spatial learning and memory of autistic rats by exercise.
Conclusion
The findings suggest that treadmill exercise can be helpful for improving some autism-like behaviors. Further studies are needed to investigate the involved mechanisms.
​​​​​​​